Acoustic and hearing-perceptual voice analysis in individuals with idiopathic Parkinson's disease in "on" and "off" stages Análise acústica e perceptivo-auditiva da voz em indivíduos com doença de Parkinson idiopática nos estágios "on" e "off" - Luiza Lara M Santos; Larissa Oliveira dos Reis; Iara Bassi; Clara Guzella; Francisco Cardoso; César Reis; Ana Cristina Côrtes Gama (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate the voice quality of patients with idiopathic Parkinson's disease, at the "on" and "off" moments of the disease. METHOD: Five individuals with Parkinson's disease and five of the control group were assessed. All of them underwent the recording of voice and speech. The acoustic parameters analyzed were: fundamental frequency, jitter, shimmer, harmonic noise proportion and index of tremor, besides performing the hearing-perceptual analysis by means of GRBASI scale. The findings were analyzed using statistics through t test and the level of significance adopted was p<0.05. RESULTS: There was no difference in the acoustic parameters in the three analyzed groups. In the hearing-perceptual analysis, patients with idiopathic Parkinson's disease showed altered voice quality and the ones from the control group, neutral vocal quality. CONCLUSION: Patients with idiopathic Parkinson's disease present rough, breathy and unstable vocal quality in both stages. In the acoustic analysis, there are no differences in the studied parameters. OBJETIVO: Avaliar a qualidade vocal de pacientes portadores da doença de Parkinson idiopática, nos momentos "on" e "off" da doença. MÉTODO: Foram avaliados 5 indivíduos com doença de Parkinson idiopática e 5 do grupo controle. Todos foram submetidos à gravação da voz e fala. Os parâmetros acústicos analisados foram: frequência fundamental, jitter, shimmer, PHR e índice de tremor, além da realização da análise perceptivo-auditiva por meio da escala GRBASI. Os achados foram analisados pelo teste t e o nível de significância adotado foi p<0,05. RESULTADOS: Não foi encontrada diferença nos parâmetros acústicos nos três grupos estudados. Na análise perceptivo-auditiva, os pacientes com doença de Parkinson idiopática apresentaram qualidade vocal alterada e os do grupo controle qualidade vocal neutra. CONCLUSÃO: Os indivíduos com doença de Parkinson idiopática apresentam qualidade vocal rugosa, soprosa e instável, em ambos estágios. Na análise acústica, não há diferenças nos parâmetros estudados.